boolean algebra

Discussion in 'Homework Help' started by Jdebeer123, Mar 12, 2011.

  1. Jdebeer123

    Thread Starter New Member

    Mar 12, 2011
    Hi there

    with regards to the question Cino had I am also having a bit of trouble.

    My effort so far is as follows then I get stuck.Please help

    F1 = x + x'(yw)' + w'y
    = 1(yw)' + w'y
    = 1(y' + w') + w'y
    = y' + w' + w'y

    I cant seem to find any rules that apply to the last one

    Also F2 = (y' + x')'
    = y + x or would it be double Not's (y'' + x'')

    Please help


    [​IMG] [​IMG]
  2. justtrying

    Active Member

    Mar 9, 2011
    from your efforts, you can keep factoring = y' + w' + w'y = y'+w'(1+y) - does (1+y) equal anything? But I think you might want to review how you got x + x'(yw)' to reduce to 1(yw)' - it is true that x+x'=1, but that is not what I see in the question, unless you missed the brackets when posting it :)